How to increase motivation and job satisfaction: Empirical case study - Oliveira, Cidália (2023)
Job satisfaction is becoming increasingly important, especially since the end of the last millennium, as there are numerous organizations that have fostered its relevance to increase job-commitment in their companies. On one side, managers have to learn how to handle and to manage efficiently the dynamic capabilities and their soft skills so as to adapt the environment in which collaborators operate. On the other side, the environment is adapted by employees. Although there is a wide research in this area, there is still a gap in the literature, as the latest literature review points to adverse situations of burnout and job stress with effects on organizational commitment, mediated by job satisfaction. Bearing this highlight in mind, this paper aims to explore the current state of research related to job satisfaction and its impact on organizational performance. It intends to analyze job satisfaction of employees towards the whole organization, as well as towards organizational managers and leaders.